Acetal-protected acrylic copolymers for dismantlable adhesives with spontaneous and complete removability. (1st May 2015) - Sato, Eriko; Yamanishi, Keisuke; Inui, Tadashi; Horibe, Hideo; Matsumoto, Akikazu
Abstract: Acetal-protected acrylic copolymers consisting of 1-isobutoxyethyl acrylate (iBEA), 2-ethylhexyl acrylate (2EHA), and 2-hydroxyethyl acrylate (HEA) repeating units were applied to the pressure-sensitive adhesive (PSA) types of dismantlable adhesives. The random and block copolymers with a relatively high HEA content showed good PSA properties before dismantling treatment. The deprotection of the acetal-protected group of the iBEA unit took place in response to individual external stimuli, soaking in boiling water and UV irradiation in the presence of a photoacid generator. The random copolymers containing an HEA unit of more than 10 mol% and an iBEA unit of more than 70 mol% achieved spontaneous debonding with interfacial failures at both the stainless steel and polyethylene terephthalate support film sides by soaking in boiling water within 10 min, whereas the corresponding block copolymer did not achieve interfacial failure even after a 20-min soaking. Photoirradiation of the random copolymers containing N -hydroxynaphthalimide triflate as a photoacid generator resulted in interfacial failures at both sides with a sufficiently reduced peel strength, where cross-linking arose due to the transacetalization and transesterification of a hydroxy group in the HEA unit along with deprotection. Graphical abstract: Highlights: The copolymers were investigated as dismantlable pressure-sensitive adhesives. The copolymers underwent deprotection and cross-linking by external stimuli. The reactions of the copolymers induced a decrease in 180° peel strength. The effects of the copolymer compositions on dismantlability were revealed. Spontaneous and complete removal of the adhesive layer were achieved.